A Dosimetric Comparison of VMAT and IMRT for Head & Neck and Pelvis Cancers - Muhammad Umar Farooq; Muhammad Basim Kakakhel; Aasia Razzaq; Nauman Amjad; Touqir Ahmad Afridi (USIM Press, 2024)
VOL. 9 NO. 1 (2023) Page (18-24)